Kemampuan Membayar Iuran Jaminan Kesehatan Nasional Bagi Nelayan di Kabupaten Jember (Ability To Pay The Premium Of National Health Insurance For Fisherman in Jember) - Widya Noormalasari; Nuryadi Nuryadi; Christyana Sandra (Pustaka Kesehatan, 2015)
National Health Insurance is an Indonesian government program which mandates by social Insurance that required for all Indonesian citizens through BPJS. Coverage by independent participation in Jember is still very small that equal to 0.75 % of all participants registered. The results of a preliminary survey on the fisherman shows that 72.5 % of respondents thought unable to pay contribution JKN. The objective of this study was to calculate the ability to pay contribution of JKN for fishermen in Jember. This study was a quantitative descriptive study conducted in 3 villages, there are Puger Wetan village subdistrict Puger, Sumberejo village subdistrict Ambulu, and Lojejer village subdistrict Wuluhan. Results showed that most of respondents monthly income was middle which was in the interval ≥Rp.3.100.000,- to ≤Rp.7.750.000,- by the average was Rp.6.200.000,-; while the average household expenditure reached up to Rp.6.077.424,-. The calculation formula has got to calculate ability to pay is ΣRevenue – (-63880+ 0,8653X + ₁ 0,6361X3+ 1,277X4+ 1,081X5+ 0,6571X6+ 1,269X7+ 1,151X8+ 1,165X9+ 0,9445X10+ 1,307X11+ 1,540X12+ 0,9707X13+ 1,007X14+ 1,159X15+ 0.9988X16+ 1,047X17+ 1,064X18+ 3,517X19+ 1,015X20). Most of respondents (54,5%) were able to pay the premium of National Health Insurance. Most of respondents (61,11%) were only having ability to paid the premium for inpatient care grade 3 (Rp.25.500,- for one person every month). Keywords : Ability To Pay, National Health Insurance, Fisherman